Rattus villosissimus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
723. Australian Long-haired Rat Rattus villosissimus French: Rat a poil long / German: Langhaarige Australische Ratte / Spanish: Rata de pelo largo de Australia Other common names: Long-haired Rat, Plague Rat Taxonomy. Mus villosissimus Waite, 1898, “Central Australia.” Identified by J. A. Mahoney and B. J. Richardson in 1988 as “probably the vicinity of Goonhag-hooheeny Billabong, Cooper Creek,” Queensland, Australia. Rattus villosissimus is in the R. sordidus species group, which clusters with the other Australian species groups. All Australian species of Rattus are sister to a cladecontaining the New Guinea endemic species, although not all species have been sampled and more research is needed to fully resolve relationships within this clade of Rattus. Monotypic. Distribution. N &C Australia in two central core areas (Barkly Lake system of the Barkly Tableland, Northern Territory, and Channel Country in SW Queensland and NE South Australia), and Southwest I, Sir Edward Pellew Group. Descriptive notes. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 851, DOI: 10.5281/zenodo.6887260 ...